Socio-Technical Transformation of Rural Agriculture: Community-Based Coffee Agroforestry Innovation in Girimekar Village - Andis Destrian Irianto; Vlaradhia Sakura Annisa Gricylla; Rizky Fadilah (Jurnal Sosioteknologi, 2026)
This study examines socio-technical transition and community-based innovation in Girimekar Village, focusing on how local actors respond to ecological pressures, institutional change, and economic opportunities. Using a qualitative case study, the research analyzes the transition from conventional vegetable farming to coffee-based agroforestry. Data were collected through in-depth interviews with farmers, village officials, Perhutani representatives, youth groups, and facilitators, plus participatory observation and analysis of village documents. The analysis combines the multi-level perspective, which explores interactions between niche, regime, and landscape levels, with actor-network theory, which captures relational dynamics between human and nonhuman actors. The findings show that the transition is not simply a change in crops but a broader socio-technical reconfiguration shaped by collective learning, hybrid knowledge systems, improved land-access arrangements, and strengthened actor networks. Coffee functions as a niche innovation that stabilizes through local experimentation, ecological suitability, and expanding markets, while PHBM schemes and village programs facilitate integration into everyday production. This study contributes to socio-technical transition literature by demonstrating how rural innovation in Indonesia emerges through negotiated community-based processes. Unlike work emphasizing technological adoption, it highlights the relational and territorial dimensions through which local knowledge, collaborative governance, and agroforestry collectively shape sustainable rural transformation.